Strategy of Takhfidzul Qur'an Learning in Madrosatul Qur'an Islamic Boarding School: Strategi Pembelajaran Tahfidzul Qur’an Di Pondok Pesantren Madrosatul Qur’an - Anas Khoirudin; Imam Fauji (Academia Open, 2022)
The aim of this study is to defer the tahdzul Koran learning strategy in madrosatul boarding hut. This type of research is qualitative research the subject of this study is the superintendent of teachers and santri present in madrosatul qur’an Islamic boarding school Surabaya. The data-gathering technique USES the interactive analysis of the data reduction. The display of data and the conclusion of the learning done at madrosatul boarding school. This study revealed that the 1 condemned Qur’an strategy of learning in madrosatul monastery was published in Madrosatul Qur’an message by growing a sense of comfort in memorizing the Qur’an. As for the strategy used in memorizing will not go to the next verse before the verse that is memorized thoroughly. Where as memorized collections were done with two new deposits and one daily amount of pure labor except for the holiday. 2 factors behind the madrosatul qur’an student, asatidza, environment, intelligence and motivation include the individual. While inhibitory factors include lazy, it includes the age, family, hails, hails, and reading.